The Effect of Lactapuncture Massage on Breast Milk Production through Prolactin Hormone Levels Changes in Dr. M. Ashari Hospital, Pemalang, Central Java - Patimah, Siti; Mashoedi, Imam Djamaluddin; Hadisaputro, Suharyo (Indonesian Journal of Medicine, 2019)
Background: Problems that inhibit breastfeeding in the first week include less breast milk production. Increasing breast milk production can be done by stimulating or massage the breast. Breast massage can be done by lactapuncture massage. This study aimed to examine the effect of lactapuncture massage on prolactin hormone levels and breast milk production among primiparous mothers.Subjects and Method: This was a quasy experiment study conducted at Dr. M. Ashari hospital, Pemalang, Central Java, Indonesia. A sample of 32 primiparous postpartum mothers was selected by simple random sampling. The dependent variable was breast milk production. The independent variables were lactapuncture massage for 7 consecutive days. The data were analyzed by t-test.Results: Prolactin hormone level in intervention group (mean= 313.80; SD= 45.54) was higher than in control group (mean= 292.09; SD= 97.87) but it was statistically non-significant (p= 0.428). Breast milk production in intervention group was higher (mean= 9.36; SD= 0.71) than in control group (mean= 7.39; SD= 0.23) and it was statistically significant (p<0.001).Conclusion: The lactapuncture massage on 2-3 times clockwise at each point for 7 consecutive days increasing prolactin hormone levels and on breast milk production.Keywords: lactapuncture massage, prolactin hormone, breast milk productionCorrespondence: Siti Patimah. Applied Midwifery, Graduate Program, School of Health Polytechnics, Ministry of Health Semarang. Email: imafatimah922@gmail.com. Mobile: 081329283952 Indonesian Journal of Medicine (2019), 4(1): 15-20https://doi.org/10.26911/theijmed.2019.04.01.03